Model Kolaboratif Pengusaha Pariwisata dan Pengungsi dalam Konteks Bencana Erupsi Gunung Agung di Desa Wisata Kerta, Kabupaten Gianyar, Bali - Saptono Nugroho; I Nyoman Sukma Arida; I Nyoman Jamin Ariana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
This article seeks to find a sustainable model of handling refugees based on the kind of social solidarity that builds between refugees and tourism entrepreneurs amid the disaster. The research took place in Kerta Tourism Village, Gianyar Regency, Bali with the consideration of the unique phenomenon of productive and professional working relationship between the two actors. This fact is seen as able to deconstruct the stereotype of refugees as a group that only needs pity, resulting in a